MUSLIM WOMEN SWITCHING INTENTION TO HALAL COSMETIC: PUSH-PULL-MOORING MODEL APPLICATION - Pambekti, Galuh Tri; Nugraha, Septy Setia; Yusfiarto, Rizaldi (Bank Indonesia, 2023)
This study focuses on the factors that contribute to switching intentions from non-halal cosmetics to halal cosmetics by Muslim women in Indonesia. Using a questionnaire and purposive sampling, we compile data from a total of 236 women who use halal cosmetics and then apply the SEM-PLS for data analysis. The results show that the pull effect significantly affects Muslim women's intention to switch to halal cosmetics and is moderated negatively by switching costs. By contrast, the push effect doesn’t significantly affect the intention to switch to halal cosmetics. In addition, halal awareness and switching costs directly affect Muslim women's switching intentions from non-halal to halal cosmetics. Acknowledgment The authors would like to thank Bank Indonesia Institute, Bank Indonesia, for the funding that made this study possible.